The role of soft tissue coverage in limb salvaging and reconstructive surgery of foot and ankle - Kow, Ren Yi; Ahmad Alwi, Akmal Azim; Abas, Muhammad Firdaus; Low, Chooi Leng (Kulliyyah (Faculty) of Medicine, International Islamic University Malaysia, 2019)
Since humans evolutionally adapt to a bipedal gait, the foot is important to allow humans to stand up, walk, run, and to jump. Without the soft tissues and bones at the foot and ankle, our lower limbs could not support the weight of the body. Crush injury of the foot and ankle is a consequence of high energy trauma leading to combined bone and soft tissue loss or destruction. The treatment of crush injury of the foot and ankle remains a challenge as it is associated with high morbidity. We report two cases of traumatic injury of foot and ankle to highlight the paramount importance of soft tissue coverage in limb salvaging and reconstructive surgery of foot and ankle.